Access to the Enantiopure Axially Chiral Cyclophane Isoplagiochin D through Atropo‐diastereoselective Heck Coupling. Issue 29 (15th June 2018) - Meidlinger, Daniel; Marx, Lisa; Bordeianu, Catalina; Choppin, Sabine; Colobert, Françoise; Speicher, Andreas
Abstract: Macrocyclization is typically the key step in the syntheses of cyclophane‐type natural products. Considering cyclophanes with axially chiral biaryl moieties, the control of atroposelectivity is essential with biological activity and is synthetically challenging. We report an atroposelective approach involving Heck cyclization, which for the first time enables the total synthesis of an enantiopure macrocyclic bis(bibenzyl), namely isoplagiochin D. An enantiopure sulfinyl auxiliary in the ortho position of a biaryl axis (still flexible) was used to induce an atropo‐diastereoselective Heck coupling (up to 98 % de). The traceless character of the sulfinyl auxiliary enables the introduction of a hydroxy group to give the target molecule with 98 % ee as well. Abstract : Triple function : A chiral sulfinyl auxiliary group in the ortho position of a biaryl axis 1) directs ortho ′‐iodination in the adjacent aryl moiety, 2) directs an atropo‐diastereoselective ortho ′‐Heck coupling with dynamic kinetic resolution, and 3) can finally be transformed into the hydroxy function of a natural occurring cyclophane type bis(bibenzyl).